Brief Report: The lincRNA Hotair Is Required for Epithelial-to-Mesenchymal Transition and Stemness Maintenance of Cancer Cell Lines - Alves, Cleidson Padua; Fonseca, Aline Simoneti; Muys, Bruna Rodrigues; Bueno, Rafaela de Barros e Lima; Buerger, Matheus Carvalho; Souza, Jorge E. S. de; Valente, Valeria [UNESP]; Zago, Marco Antonio; Silva, Wilson Araujo (Wiley-Blackwell, 2013)
Hotair is a member of the recently described class of noncoding RNAs called lincRNA (large intergenic noncoding RNA). Various studies suggest that Hotair acts regulating epigenetic states by recruiting chromatin-modifying complexes to specific target sequences that ultimately leads to suppression of several genes. Although Hotair has been associated with metastasis and poor prognosis in different tumor types, a deep characterization of its functions in cancer is still needed. Here, we investigated the role of Hotair in the scenario of epithelial-to-mesenchymal transition (EMT) and in the arising and maintenance of cancer stem cells (CSCs). We found that treatment with TGF-1 resulted in increased Hotair expression and triggered the EMT program. Interestingly, ablation of Hotair expression by siRNA prevented the EMT program stimulated by TGF-1, and also the colony-forming capacity of colon and breast cancer cells. Furthermore, we observed that the colon CSC subpopulation (CD133(+)/CD44(+)) presents much higher levels of Hotair when compared with the non-stem cell subpopulation. These results indicate that Hotair acts as a key regulator that controls the multiple signaling mechanisms involved in EMT. Altogether, our data suggest that the role of Hotair in tumorigenesis occurs through EMT triggering and stemness acquisition.
Keywords: Cancer stem cell; Epithelial-to-mesenchymal transition; LincRNA; Hotair